Oral health-related quality of life as a predictor of subjective well-being among older adults: a decade-long longitudinal cohort study - Klotz, Anna-Luisa; Tauber, Benjamin; Schubert, Anna-Lena; Hassel, Alexander J.; Schröder, Johannes; Wahl, Hans-Werner; Rammelsberg, Peter; Zenthöfer, Andreas (Community dentistry and oral epidemiology, 2018)
The objective of this study was to evaluate possible longitudinal associations between oral health-related quality of life (OHRQoL) and subjective well-being among quinquagenarians and septuagenarians over up to 10 years of clinical observation.